Review on preparation and evaluation of herbal mosquito repellent - Kollu, Srihridya (International Journal of Indigenous Herbs and Drugs, 2025)
Mosquito-borne diseases such as malaria, dengue, chikungunya, Zika virus infection, lymphatic filariasis, and Japanese encephalitis remain major global health concerns, especially in tropical and developing regions. Although synthetic mosquito repellents like DEET and allethrin are commonly used, their long-term application has been associated with adverse health effects and environmental hazards. As a result, there is growing interest in herbal mosquito repellents that are safer, biodegradable, and environmentally friendly. This study focuses on the preparation and evaluation of herbal mosquito repellent sticks formulated using natural ingredients such as neem (Azadirachta indica), tulasi/holy basil (Ocimum sanctum), clove (Syzygium aromaticum), cinnamon bark (Cinnamomum species), camphor (Cinnamomum camphora), and eucalyptus oil (Eucalyptus globulus). Supportive materials such as charcoal, sawdust, and starch were also incorporated. These plant-based ingredients contain bioactive compounds known for their mosquito repellent, insecticidal, and larvicidal properties.The prepared dhoop sticks were evaluated for physical appearance, moisture content, smoke toxicity, irritation potential, mosquito repellent activity, ash value, smoke visibility, mosquito landing test, and user feedback. The findings suggest that herbal mosquito repellents offer advantages such as low toxicity, pleasant aroma, and environmental safety. However, limitations including shorter duration of protection and variable efficacy were observed. Further improvements in formulation and standardization may enhance their effectiveness and acceptance as sustainable alternatives to chemical repellents.